Photosynthetic Capacity, Antioxidant Activity and Molecular Responses in Parthenocissus Quinquefolia (L.) Planch Under High Temperature Stress and Subsequent Recovery (Bangladesh Journal of Botany, 2021)
Photosynthetic capacity and photosystem II (PSII) activity decreased with increasing temperature, whereas antioxidant enzyme activity showed the opposite trend. High temperature stress induced a significant increase in Φf,D, and D1 protein turnover rate. Photosynthetic capacity, PSII activity, and antioxidant enzyme levels in plants treated at 35 and 40°C were restored to control levels upon stress relief, whereas those in plants grown at 45℃ were only partially restored. Therefore, the temperature limit for heat tolerance in Parthenocissus quinquefolia is between 40 and 45℃. Further, it was observed that antioxidant enzymes were crucial for high-temperature stress resistance in P. quinquefolia, with DEGP1 protein playing a major role in the rapid turnover of D1 protein for PSII repair.Bangladesh J. Bot. 50(2): 433-436, 2021 (June)